Model Pembelajaran Matematika Realistik sebagai Optimalisasi Kecerdasan Logika Matematika pada Siswa SD/MI - Musrikah, Musrikah (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
Human being is blessed with intelligence from his birth. Generally, there are 9 types of human intelligence. Each person has different types of intelligence. One type of intelligence is logic mathematic. This type related with someoneâs ability to solve the problem. He/ She is able to think and construct solution with logical order and great interest in numbers, logic, order and seriation(regularity). This type of intelligence usually can be detected from oneâs mastery of mathematic. Logic mathematic intelligence can be increase by using the appropriate learning model. One of learning model is Realistic Mathematic Education with has five characteristics, they are: using context, using model, student contribution, interactivity, and intertwining.